2001
DOI: 10.1007/bf02317798
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and cross-spectral autoregressive analysis of cardiovascular variables in subjects with different degrees of orthostatic tolerance

Abstract: The mechanisms leading to vasovagal syncope are still unclear. A simple discriminating test for the identification of syncopeprone subjects is not presently available. Fifty-two subjects had a stepwise orthostatic test with 60 ~ tilt and -20 and -40 mm Hg lower-body negative pressure before the appearance of impending syncope symptoms. Spectral and cross-spectral analyses of heart period and systolic pressure time series were performed to estimate the power of the high-frequency (= 0.25 Hz) and low-frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
(65 reference statements)
6
20
0
Order By: Relevance
“…Although the increased cardiac baroreflex delay of ϳ1.3 s in cervical SCI subjects may seem small, it represents an increased latency of ϳ70%, which is not inconsiderable. Similar increases in latency have been seen in other pathological conditions of blood pressure regulation (21)(22)(23)(24) and in the elderly (50), in whom baroreflex responses and blood pressure control are impaired (40,41). However, the cross-spectral estimates of cardiac baroreflex function may or may not be reflected in baroreflex control of sympathetic vascular regulation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although the increased cardiac baroreflex delay of ϳ1.3 s in cervical SCI subjects may seem small, it represents an increased latency of ϳ70%, which is not inconsiderable. Similar increases in latency have been seen in other pathological conditions of blood pressure regulation (21)(22)(23)(24) and in the elderly (50), in whom baroreflex responses and blood pressure control are impaired (40,41). However, the cross-spectral estimates of cardiac baroreflex function may or may not be reflected in baroreflex control of sympathetic vascular regulation.…”
Section: Discussionsupporting
confidence: 61%
“…was also less coherence in the cervical SCI group in the upright position, which may be a consequence of increased reflex delay and subsequent failure to engage the baroreflex. Interestingly, increased cardiac (21,22,24) and vascular resistance (23) baroreflex delay have been implicated in other disorders of blood pressure control and are associated with reduced coherence (22). Increased baroreflex delay is proposed to lead to instability of blood pressure homeostasis and an increased risk of orthostatic intolerance (21), a common feature in subjects with cervical SCI (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compensatory mechanisms mainly involve an increase in total peripheral vascular resistance (Brown and Hainsworth 2000) that is mediated by enhanced sympathetic outflow (Kimmerly and Shoemaker 2002;Levine et al 2002). As in other studies (Cooke et al 1999;Gulli et al 2001), we found that MAP was well maintained during the steady-state orthostatic stress, with no change in the LF power of RR-interval oscillations but with an increase in the power of LF spontaneous blood pressure oscillations. The enhanced blood pressure oscillations were not transmitted onto the cerebral circulation, indicating that autoregulation protects the cerebral vessels from sympathetically mediated perturbations in blood pressure.…”
Section: Discussionsupporting
confidence: 61%
“…Although assessing gain of a closed-loop system can be achieved by observing spontaneously occurring input and output fluctuations, the system must encompass only feedback relations, the fluctuations must be sufficiently large, and the gain must be linear across all ranges. Yet heart rate fluctuations represent both feedback and feedforward aspects of the cardiovascular system, 55 spontaneous fluctuations can at times be immeasurably small (eg, Gulli et al 56 ), and baroreflex gain is characteristically nonlinear across its range. 49 The alternative to observation is to drive the system; ie, to open the loop and observe the gain.…”
Section: Spontaneous and Direct Estimates Of Baroreflex Gainmentioning
confidence: 99%